Approximation of holomorphic functions by Taylor-Abel-Poisson means - Savchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We investigate approximations of functions f holomorphic in the unit disk by means A_ρ, r(f) for ρ → 1_-. In terms of an error of the approximation by these means, the constructive characteristic of classes of holomorphic functions H_p^r Lip α is given. The problem of the saturation of A_ρ, r(f) in the Hardy space H_p is solved.